Mechanisms of an App-Based Physical Activity Intervention and Maintenance in Community-Dwelling Women: Mediation Analyses of a Randomized Controlled Trial. Issue 2 (5th March 2023) - Fukuoka, Yoshimi; Haskell, William; Vittinghoff, Eric
Abstract : Background: Understanding the mechanism of interventions that increase physical activity (PA) is critical to developing robust intervention strategies. Aims: This study aims to examine the mediation effects of hypothesized changes in self-efficacy, social support, and barriers on daily changes in accelerometer-measured steps and the duration of moderate to vigorous PA over 3-month intervention and 6-month maintenance periods with a mobile phone–based PA education program. Methods: Data were analyzed for a total of 210 physically inactive women who were randomized. The mean (SD) age was 52.4 (11.0) years. The framework of Baron and Kenny and the Sobel test were used to evaluate the proportion of the treatment effect explained by mediation factors. Results: Postintervention PA changes were mediated by a reduction in self-efficacy and barriers and an increase in social support from friends during the intervention and maintenance periods ( P ≤ .05). However, social support from family was significant only during the intervention, but not the maintenance ( P = .90). Barriers to PA had the largest mediation effect on the intervention, explaining 13% to 16% of the 3-month intervention effect and 14% to 19% of the 6-month maintenance effect on daily steps and duration of moderate to vigorous PA minutes ( P ≤ .05). Conclusions: Incorporating strategies for overcoming PA barriers and promoting social support for PA is important for the design of interventions for physically inactive women. However, a reduction in self-efficacy was observed in the intervention group at 3 and 9 months as compared with the control group. This unexpected finding requires further investigation.